Effect of Extraction Conditions on Total Polyphenol and Flavonoid Content of Sugar Apple Seeds (Annona squamosa L.) - Nguyen, Van Thuy; Nguyen, Ngoc Quy; Muoi, Nguyen Van; Cang, Mai Huynh (Asian Journal of Chemistry, 2020)
The objective of this study was to determine the optimal value of factors affecting the extraction of phenolic compounds from sugar apple seeds. The effects of solvent nature (ethanol, methanol and water), solvent concentration (40, 60,80 and 100%), solid-to-solvent ratio (2.5/100, 5.0/100, 7.5/100 and 10 mg/100 mL), extraction temperature (40, 50, 60 and 70 ºC) and extraction time (60, 120, 180 and 240 min) were investigated. Total phenolic content and total flavonoid content were used for the determination of phenolic compounds of sugar apple seeds extract. Experimental results showed that all the examined parameters had statistically significant (p < 0.05) effects on phenolic compound extraction. The optimal extraction conditions were as follows: extracting solvent 80% ethanol, sample-to-solvent ratio 5 g/100 mL, extraction contact time 120 min and extraction temperature 60 ºC with values of 356.92 ± 9.27 mgGAE/100g DW, 240.03 ± 6.16 mgQE/100g DW for the total phenolic content and the total flavonoid content, respectively.